Eksplorasi Kebutuhan Finansial Karyawan terhadap Sistem Penggajian Berbasis Kripto: Studi Fenomenolog - Kurniawan, Agung Widhi (PT Maju Malaqbi Makkarana, 2025)
This research aims to explore employees' financial needs for a crypto-based payroll system through a phenomenological approach. Using qualitative methods, the research involved in-depth interviews with 15 employees from various industry sectors who received salaries in crypto or tokens for at least six months. The research findings revealed three main themes: (1) the dichotomy between the flexibility of cross-border transactions and the uncertainty of crypto-value volatility, (2) the crucial role of financial literacy in determining employees' level of adaptation, and (3) the importance of company support and clear regulations. The results showed that while 73% of participants appreciated the system's efficiency, 85% were concerned about the instability of asset values impacting their financial planning. This study reinforces previous findings (Zhang et al., 2022; Lee & Wang, 2021) on the complexity of innovative financial technology adoption at the individual level. The implications of the study emphasize the need for hybrid (crypto-fiat) policies, specialized financial education programs, and a regulatory framework that protects workers' rights without stifling innovation. The findings significantly contribute to the development of sustainable payroll systems in the digital economy.